2021
DOI: 10.1080/21655979.2021.1877413
|View full text |Cite
|
Sign up to set email alerts
|

Bio-herbicidal potential of wheat rhizosphere bacteria on Avena fatua L. grass

Abstract: In order to isolated and identified the bacterial strains from wheat rhizosphere and evaluated the effect of different concentration of bacterial fermentation broth on the wild oats weed growth. This experiment carried out the separation and purification of dominant bacterial strains from the wheat rhizosphere soil, and performed the fermentation broth biological activity assessment by measured the seed germination and plant growth from 20 wheat varieties. The results had shown that the bacterial fermentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…The Accordingly, the correlation of bacterial communities was more complex than fungi, and fungicides reduced the complexity of microbial symbiosis network which is due to the reduction of functional microorganisms and consistent with Fournier et al and Li et al [39][40]. The main prevailed of Proteobacteria and Ascomycota in fungicide treated soil indicated high resistance to chemical, similarly result also found in previous study [41][42][43][44].…”
Section: 4the Correlation Of Predominant Bacterial and Fungal Communitiessupporting
confidence: 89%
“…The Accordingly, the correlation of bacterial communities was more complex than fungi, and fungicides reduced the complexity of microbial symbiosis network which is due to the reduction of functional microorganisms and consistent with Fournier et al and Li et al [39][40]. The main prevailed of Proteobacteria and Ascomycota in fungicide treated soil indicated high resistance to chemical, similarly result also found in previous study [41][42][43][44].…”
Section: 4the Correlation Of Predominant Bacterial and Fungal Communitiessupporting
confidence: 89%
“…A more popular method involves the direct use of weed seeds to screen PAB for the inhibition of seed germination; this has been carried out using the seeds of Orobanche sp. [ 27 ], Parthenium hysterophorus [ 28 ], Bromus tectorum [ 29 ], Avena fatua [ 30 ], and Chenopodium album [ 31 ], etc. The seeds of all species of weeds can be used to screen for microbes producing the phytotoxic metabolites that inhibit seed germination.…”
Section: Rapid Screening For Plant-associated Bacteria With Herbicida...mentioning
confidence: 99%
“…Li et al isolated several herbicidal strains of rhizobacteria against wild oat, and one of the strains, Bacillus sp. X20, inhibited the germination of seeds of wild oat by 75% [ 30 ]. P. fluorescens strain L2-19, S. maltophilia strain TFR1, and P. putida strain B1-7 isolated from the rhizosphere of green foxtail significantly reduced the growth of green foxtail [ 87 ].…”
Section: Phytotoxic or Herbicidal Rhizobacteriamentioning
confidence: 99%
“…Microorganisms play an important role in plant growth. 13 ,separated and purified dominant bacterial strains from wheat rhizosphere soil and found that the superior bacterial strain X20 was Bacillus , which is a potential inhibitor for developing bacterial-based bioherbicides for wild oats weed control management in wheat fields. Although a close relationship exists between soil microorganisms and plants, few reports exist regarding the microbial diversity of plant soil.…”
Section: Introductionmentioning
confidence: 99%